Influence of relationship quality and severity of aggression on post-conflict affiliation in Hamadryas Baboons - Neo, Frederick Chern Ee (2009)
Aggression and post-conflict behaviours in hamadryas baboons (Papio hamadryas hamadryas) are being examined in this study. The relationship quality between the pairs of baboons which had just fought and levels of aggression were used to predict reconciliation and triadic post-conflict affiliation for hamadryas baboons. We found that relationship quality is able to positively predict both reconciliation and triadic post-conflict affiliation. Levels of aggression did not have a significant effect on reconciliation but it was found that proximity between aggressors and third parties was highest at moderate levels of aggression. Furthermore it was found that triadic post-conflict affiliations were higher for aggressors than they were for victims of aggression. The implications of these findings are discussed.